ANALISIS PENGARUH PEMBANGUNAN KANTOR PUSAT PEMERINTAHAN KABUPATEN MIMIKA TERHADAP PERTUMBUHAN WILAYAH DI SP3 KELURAHAN KARANGSENANG - Jermin, Jermin; Rumansara, Enos H.; Rante, Harmonis (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2024)
In this study, the researcher discusses the analysis of the impact of the development of Mimika Regency's government headquarters on regional growth in SP3 Karangsenang Village. The goals of this study are to look into how the development of the government headquarters of Mimika Regency has affected regional growth in the Kuala Kencana District of SP3 Karangsenang Village, what those effects mean, and what factors affect the development of the government headquarters of Mimika Regency on regional growth in the Kuala Kencana District of SP3 Karangsenang Village. The study employs scalogram analysis to assess Karangsenang Village's viability as a growth center, considering the availability of facilities. We expect the study's results to shed light on how development affects a region's growth.